The Effect of Snakes and Ladders Game on the Level of Gadget Addiction in School-Age Children - Raras Arifa Kinanti Putri; Dwi Indah Iswanti; Umi Hani; Son Haji (CV LINK Education Publication, 2024)
Introduction: The development of technology is marked by the widespread use of gadgets not only by adults, but children also have the same interest. Excessive intensity of gadget use can indicate addiction to gadget use. Children's dependence on gadgets is due to the convenience and sophistication features contained in them, however, the games on gadgets make children less active, have less emotional expression, have minimal self-awareness, and have minimal social interaction with peers because they make children only fixated on their gadget screens. Previous research has revealed that actively play with peers can have a positive influence on children's gadget addiction, playing with peers can also be used as an effort to stimulate aspects of child development. Objectives: This research aims to determine the effect of the snakes and ladders game on the level of gadget addiction in school-age children at SDN Sendangmulyo 02 Semarang. Methods: This is quasi-experimental research with one-group pretest-posttest design. Purposive sampling was used as the sampling technique with 18 school-age children as respondents. This research used the Shapiro-Wilk Normality Test and the Wilcoxon Signed Ranks Test was used as the hypothesis test. Results: The results of the study analyzed using the Wilcoxon Signed Ranks Test showed a p-value <0.05, which is 0.000. Conclusion: Based on analysis results can be concluded that the snakes and ladders game influences the level of gadget addiction in school-age children.